Exposure and engagement with tobacco-related social media and associations with subsequent tobacco use among young adults: A longitudinal analysis. (1st August 2020) - Clendennen, Stephanie L.; Loukas, Alexandra; Vandewater, Elizabeth A.; Perry, Cheryl L.; Wilkinson, Anna V.
Highlights: One-third of young adults reported past 30-day exposure to social media tobacco advertising. One-fourth of young adults reported ever engaging with tobacco-related social media. Engagement with anti-tobacco messaging was more prevalent than pro-engagement. Exposure and engagement were significantly associated with subsequent tobacco use. Abstract: Background: This study examines whether self-reported exposure to cigarette, e-cigarette, cigar, and hookah advertising, and engagement with pro-tobacco and anti-tobacco social media, are associated with past 30-day tobacco use one-year later, among young adults. Methods: Data were from two waves of the Marketing and Promotions Across Colleges in Texas study, a multi-wave study of two- and four-year Texas college students ( N = 3947; M age = 23.3, SD = 2.3; 64% female; 35% white, 31% Hispanic, 19% Asian, 8% African-American/black, 7% multi-racial/other) from 24 urban-area schools. Multiple logistic regression examined longitudinal associations between recall of exposure and engagement at baseline (wave 6, spring 2017) and tobacco use at one-year follow-up (wave 7, spring 2018), accounting for baseline demographic characteristics and tobacco use. Results: Self-reported exposure to and engagement with tobacco-related social media were significantly associated with past 30-day use of e-cigarettes, cigars, and hookah at one-year follow up; engagement was also associated with cigarette use. Controlling for other social media, exposure to any product advertising via Reddit increased risk for e-cigarette use (AOR = 1.92 [95% CI: 1.17–3.14]). Pinterest exposure increased risk for cigar use (2.92 [1.24–6.85]). Snapchat exposure increased risk for hookah use (2.94 [1.70–5.11]). Pro-tobacco engagement increased risk for future use of all products (1.77 [1.29–2.42]). Anti-tobacco engagement increased risk for use of cigars (1.59 [1.12–2.27]) and hookah (1.69 [1.27–2.25]). Conclusions: Findings demonstrate that encountering tobacco-related social media is an important risk factor for future tobacco use among young people. Social media should be a focus of federal regulation, counter-marketing and health communication campaigns, and intervention.